Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Vì \(a+b+c=0\Rightarrow a+b=-c\)
Ta có:
\(a^3+b^3+c^3=\left(a+b\right)^3-3ab\left(a+b\right)+c^3=\left(-c\right)^3-3ab.\left(-c\right)+c^3=3abc\)
Do đó, với \(abc=3\) thì \(a^3+b^3+c^3=3.3=9\)
(a+b+c)3=[(a+b)+c]3=(a+b)3+c3+3(a+b)c(a+b+c)
=a3+b3+3ab(a+b)+c3+3(a+b)c(a+b+c)
=a3+b3+c3+3(a+b)[ab+c(a+b+c)]
=a3+b3+c3+3(a+b)(ab+ac+bc+c2)
==a3+b3+c3+3(a+b)[(ab+ac)+(bc+c2)]
=a3+b3+c3+3(a+b)(a+c)(b+c)
#)Giải :
\(a^3+b^3+c^3+3\left(a+b\right)\left(b+c\right)\left(c+a\right)\)
\(=a^3+b^3+c^3+3\left(a+b\right)\left(ab+ac+ca+c^2\right)\)
\(=a^3+b^3+3ab\left(a+b\right)+c^3+3\left(a+b\right)c\left(a+b+c\right)\)
\(=\left(a+b^3\right)+c^3+3\left(a+b\right)c\left(a+b+c\right)\)
\(=\left(a+b+c\right)^3\)
\(\Rightarrowđpcm\)
a) \(9c^2-6c+3\)
\(=\left(9c^2-6c+1\right)+2=\left(3c-1\right)^2+2>0\)
b) \(14m-6m^2-13\)
\(=-6.\left(m^2-\frac{7}{3}m+\frac{13}{6}\right)\)
\(=-6.\left(m^2-2\cdot\frac{7}{6}\cdot m+\frac{49}{36}+\frac{29}{36}\right)\)
\(=-6.\left(m-\frac{7}{6}\right)^2-\frac{29}{6}< 0\)
c) \(a^2-2a+2=\left(a-1\right)^2+1>0\)
d) \(6b-b^2-10=-\left(b^2-6b+9\right)-1=-\left(b-3\right)^2-1< 0\)